SUSTAINABLE DEVELOPMENT OF RURAL ENVIRONMENT BY INNOVATION IN TOURISM - Simona, Bălășescu; Marius, Bălășescu (PEOPLE: International Journal of Social Sciences, 2019)
Tourism is today a mass phenomenon, with serious implications in the economic, social domain and in population welfare from the areas where it is practiced. In this paper we have studied the village Viscri - an example of success in the development of sustainable rural tourism by innovation and originality. Viscri is a Saxon village located in the commune Buneşti in Braşov County, Romania. As early as the 2000s, the local community in Viscri, supported by the Mihai Eminescu Trust Foundation (MET) has managed to develop a tourism concept that is based on the local population. By developing a new concept of tourism organization, Viscri inhabitants have proved that Romanian villages can attract tourists by creating a stable and sustainable system of tourism by capitalizing on all resources, from the human capital to the traditions, customs, and stories of an area. In the paper, we will analyze, by means of a quantitative marketing study, the perceptions of the inhabitants in Viscri about the development of rural tourism. The research aims at identifying the underlying aspects for the development of sustainable tourism in the village Viscri by studying the way of thinking and behavior of the locals.